Low birth weight and prematurity as predictors of children's receiving special education services. Issue 5 (4th April 2022) - Chen, Chin-Chih; Xu, Yaoying; Spence, Christine; Zhang, Fa; Brown Ruiz, Amber
ABSTRACT: Low birth weight (LBW) and prematurity have been identified as health risks associated with adverse developmental and educational outcomes. This study examined whether such risks affected children's receiving special education services. Using a nationally representative sample from the Pre-Elementary Educational Longitudinal Study, we investigated how LBW and prematurity affected the time when children's health and developmental concerns were raised and when children received special education services, respectively, using survival analysis. We also estimated the timing of special education services after identification of health and development concerns. Findings indicated that LBW and prematurity did not affect the time when children's developmental concerns were raised. However, they significantly predicted children's receiving earlier special education services. Specifically, after children's health and developmental concerns being initiated, those born prematurely appeared to receive services earlier at any given point of time. Implications of early detection and intervention services for these children are discussed.